Theory of nonvolatile resistive switching in monolayer molybdenum disulfide with passive electrodes - Sanchali Mitra (Nature Portfolio, 2021)
Abstract Resistive-memory devices promise to revolutionize modern computer architecture eliminating the data-shuttling bottleneck between the memory and processing unit. Recent years have seen a surge of experimental demonstrations of such devices built upon two-dimensional materials based metal–insulator–metal structures. However, the fundamental mechanism of nonvolatile resistive switching has remained elusive. Here, we conduct reactive molecular dynamics simulations for a sulfur vacancy inhabited monolayer molybdenum disulfide-based device with inert electrode systems to gain insight into such phenomena. We observe that with the application of a suitable electric field, at the vacancy positions, the sulfur atom from the other plane pops and gets arrested in the plane of the molybdenum atoms. Rigorous first principles based calculations surprisingly reveal localized metallic states (virtual filament) and stronger chemical bonding for this new atomic arrangement, explaining the nonvolatile resistive switching. We further observe that localized Joule heating plays a crucial role in restoring the popped sulfur atom to its original position. The proposed theory, which delineates both unipolar and bipolar switching, may provide useful guidelines for designing high-performance resistive-memory-based computing architecture.